2019
DOI: 10.1158/1541-7786.mcr-18-1343
|View full text |Cite
|
Sign up to set email alerts
|

HILPDA Regulates Lipid Metabolism, Lipid Droplet Abundance, and Response to Microenvironmental Stress in Solid Tumors

Abstract: Accumulation of lipid droplets has been observed in an increasing range of tumors. However, the molecular determinants of this phenotype and the impact of the tumor microenvironment on lipid droplet dynamics are not well defined. The hypoxia-inducible and lipid droplet associated protein HILPDA is known to regulate lipid storage and physiologic responses to feeding conditions in mice, and was recently shown to promote hypoxic lipid droplet formation through inhibition of the rate-limiting lipase adipose trigly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 61 publications
8
56
0
Order By: Relevance
“…Knockdown of HILPDA increased lipid droplet-derived fatty acid mobilization, due to less suppression of ATGL activity, resulting in increased fatty acid oxidation and ROS production, and impaired the growth of HCT116 colon carcinoma and HeLa tumor xenograft growth [ 130 ]. Similar observations were reported in HILPDA loss-of-function studies in HCT116 colon carcinoma models [ 132 ]. Overall, reduced ATGL activity, via knockdown of ATGL or ABHD5, has similar effects on cancer cell proliferation and viability as increased ATGL activity, via overexpression of ATGL or knockdown of HILPDA.…”
Section: Tumor Fatty Acid Metabolism Pathways and Their Role In Cancesupporting
confidence: 89%
See 2 more Smart Citations
“…Knockdown of HILPDA increased lipid droplet-derived fatty acid mobilization, due to less suppression of ATGL activity, resulting in increased fatty acid oxidation and ROS production, and impaired the growth of HCT116 colon carcinoma and HeLa tumor xenograft growth [ 130 ]. Similar observations were reported in HILPDA loss-of-function studies in HCT116 colon carcinoma models [ 132 ]. Overall, reduced ATGL activity, via knockdown of ATGL or ABHD5, has similar effects on cancer cell proliferation and viability as increased ATGL activity, via overexpression of ATGL or knockdown of HILPDA.…”
Section: Tumor Fatty Acid Metabolism Pathways and Their Role In Cancesupporting
confidence: 89%
“…ATGL overexpression did suppress melanoma, lung, and liver cancer cell proliferation [ 131 ]. We and others have shown that ATGL protein levels, and TG levels, are increased in colon, breast, and prostate cancer cells in response to high levels of extracellular fatty acids [ 3 , 4 , 132 ] and co-culturing with adipocytes [ 133 ], which also increase cell proliferation. Importantly, we also showed that the increase in ATGL protein and intracellular TG levels increased the rate of mitochondrial oxidation of TG-derived fatty acids in breast and prostate cancer cells [ 3 , 4 ].…”
Section: Tumor Fatty Acid Metabolism Pathways and Their Role In Cancementioning
confidence: 99%
See 1 more Smart Citation
“…43 Additionally, studies show that HILPDA is involved in triglyceride fatty acid secretion 44 and regulates lipid metabolism and hypoxia-induced lipid droplet biogenesis. 45 When we investigated lipid droplet accumulation in our 3D GBM organoid model, we discovered that lipid droplets were exclusively enriched in the hypoxic core region of the 3D organoids. We further traced this finding back to patients, showing that all patients in our panel with clear pseudopalisading necrosis by pathology, and most patients overall, accumulate lipid droplets in the hypoxic regions of their tumors.…”
Section: Discussionmentioning
confidence: 98%
“…This phenomenon results from FA oxidation process, activated by patatin like phospholipase domain containing 2 (PNPLA2) and mitochondrial electron leakage, which both lead to oxidative stress. To counteract this phenomenon, cancer cell downregulate PNPLA2 through the hypoxia-inducible protein 2, to promotes cancer cell survival [130,131]. The resistance to oxidative stress in hypoxic condition is also driven by a deregulated membrane lipid saturation, with increased saturated and monounsaturated FAs, which are less susceptible to peroxidation [132].…”
Section: Fatty Acids As a Metabolic Reservoir For Cancer Cell Plasticitymentioning
confidence: 99%